2017
DOI: 10.3390/ijerph14040342
|View full text |Cite
|
Sign up to set email alerts
|

Slum Upgrading and Health Equity

Abstract: Informal settlement upgrading is widely recognized for enhancing shelter and promoting economic development, yet its potential to improve health equity is usually overlooked. Almost one in seven people on the planet are expected to reside in urban informal settlements, or slums, by 2030. Slum upgrading is the process of delivering place-based environmental and social improvements to the urban poor, including land tenure, housing, infrastructure, employment, health services and political and social inclusion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 49 publications
2
48
0
1
Order By: Relevance
“…An equitable approach to arresting the COVID-19 pandemic must change standard ways of treating the urban poor, create more participatory governance, improve the delivery of essential services including health care, and invest new resources to ensure urban informal settlements benefit in the long term [13]. However, governments have already begun to impose draconian quarantine and physical distancing measures for the urban poor without also ensuring that those residing in urban slums can meet their everyday needs, such as food and clean water [14].…”
Section: Introductionmentioning
confidence: 99%
“…An equitable approach to arresting the COVID-19 pandemic must change standard ways of treating the urban poor, create more participatory governance, improve the delivery of essential services including health care, and invest new resources to ensure urban informal settlements benefit in the long term [13]. However, governments have already begun to impose draconian quarantine and physical distancing measures for the urban poor without also ensuring that those residing in urban slums can meet their everyday needs, such as food and clean water [14].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the relationship between slums and health has produced some reviews in recent years. The connection between slums and health was generally pointed out [2,3,47], as well as the connection between slum upgrading and health [5]. It was also shown that the physical environment and infrastructure intervention, such as road paving or water supply, have significant effects on the health of slum dwellers [48].…”
Section: Information On Healthmentioning
confidence: 99%
“…The inhabitants of these settlements form a separate social group [27] that is exposed to increased health risks [2], and is associated with insufficient access to infrastructures such as sanitary facilities or water supply and inadequate housing situations. These settlements are often self-built and rarely recognized by the local or national governments [5].…”
Section: Information On Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Today's cities are too often characterized by stark inequality, between the wealthy and poor and different racial/ethnic groups, among other differences. Urban informal settlements are some of the starkest manifestation of the failure of urbanization to create equitable and healthy living conditions [4]. Epidemiologists and others continue to measure population differences in health status, and urban health education will need to link these analyses to emerging methods that capture multiple and cumulative exposures in urban settings.…”
Section: Toward a New Model Of Urban Health Educationmentioning
confidence: 99%